2019
DOI: 10.1111/ocr.12322
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of orthodontic enamel demineralization: A systematic review with meta‐analyses

Abstract: Aim of this systematic review was to assess the efficacy of preventive interventions against the development of white spot lesions (WSLs) during fixed appliance orthodontic treatment. Nine databases were searched without limitations in September 2018 for randomized trials. Study selection, data extraction and risk of bias assessment were done independently in duplicate. Random‐effects meta‐analyses of mean differences (MDs) or relative risks (RRs) with their 95% confidence intervals (CIs) were conducted, follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 53 publications
(59 reference statements)
0
46
0
Order By: Relevance
“…Some of these interventions have been shown to reduce the incidence of WSL 23 , 26 , 27 . Indeed, two systematic reviews revealed that sealants were associated with reduced WSL incidence than no sealant 28 , 29 . However, only up to eight studies were included in each systematic review although there are more clinical studies that analyse coating agents.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these interventions have been shown to reduce the incidence of WSL 23 , 26 , 27 . Indeed, two systematic reviews revealed that sealants were associated with reduced WSL incidence than no sealant 28 , 29 . However, only up to eight studies were included in each systematic review although there are more clinical studies that analyse coating agents.…”
Section: Introductionmentioning
confidence: 99%
“…Together with pit and fissure sealants 5 and parent’s motivation 6 the application of fluoride is the oldest aid for caries prevention 7 . It was reported in a recent meta-analysis 8 that active patient reminders and flat surface sealants or fluoride varnish around orthodontic brackets might be associated with reduced white-spot-lesion burden, but the authors conclude that further research is needed. As another novel approach the use of bioactive glass (Biomin F paste) was shown to be an effective method for enamel remineralisation 9 .…”
Section: Introductionmentioning
confidence: 93%
“…It is widely accepted that orthodontic treatment lasts for a long time; an average treatment with fixed appliances approximately lasts 24.9 months [ 10 ]. Considering that long-treatment times are a burden to the patients and are associated with various adverse effects [ 11 , 12 ], the ability to predict treatment duration and accordingly inform patients in advance is an essential skill for orthodontists [ 13 ] and lies in the interest of both orthodontists and patients. In that context, patients’ age might be an important factor in predicting treatment duration.…”
Section: Introductionmentioning
confidence: 99%